Answer:
wavelength will be 0.686 m
So option (b) is correct
Explanation:
We have given vibration in one second that is frequency = 500 Hz
We know that velocity of sound is 343 m/sec
We have to find the wavelength
We know that velocity is given by
So wavelength
So wavelength will be 0.686 m
So option (b) is correct
Answer:
(a) t=3.87 s :time at which Kathy overtakes Stan
(b) d=37.36 m
(c) vf₁ = 15.097 m/s : Stan's final speed
vf₂ = 19.31 m/s : Kathy's final speed
Explanation:
kinematic analysis
Because Kathy and Stan move with uniformly accelerated movement we apply the following formulas:
vf= v₀+at Formula (1)
vf²=v₀²+2*a*d Formula (2)
d= v₀t+ (1/2)*a*t² Formula (3)
Where:
d:displacement in meters (m)
t : time in seconds (s)
v₀: initial speed in m/s
vf: final speed in m/s
a: acceleration in m/s²
Nomenclature
d₁: Stan displacement
t₁ : Stan time
v₀₁: Stan initial speed
vf₁: Stan final speed
a₁: Stan acceleration
d₂: car displacement
t₂ : Kathy time
v₀₂: Kathy initial speed
vf₂: Kathy final speed
a₂: Kathy acceleration
Data
v₀₁ = 0
v₀₂ = 0
a₁ = 3.1 m/s²
a₂= 4.99 m/s²
t₁ = (t₂ +1) s
Problem development
By the time Kathy overtakes Stan, the two will have traveled the same distance:
d₁ = d₂
t₁ = (t₂ +1)
We aplpy the Formula (3)
d₁ = v₀₁t₁ + (1/2)*a₁*t₁²
d₁ = 0 + (1/2)*(3.1)*t₁²
d₁ = 1.55*t₁² ; Stan's cinematic equation 1
d₂ = v₀₂t₂ + (1/2)*a₂*t₂²
d₂ = 0 + (1/2)*(4.99)*t₂²
d₂ = 2.495* t₂² : Kathy's cinematic equation 2
d₁ = d₂
equation 1=equation 2
1.55*t₁² = 2.495* t₂² , We replace t₁ = (t₂ +1)
1.55* (t₂ +1) ² =2.495* t₂²
1.55* (t₂² +2t₂+1) =2.495* t₂²
1.55*t₂²+1.55*2t₂+1.55 = 2.495* t₂²
1.55t₂²+3.1t₂+1.55=2.495t₂²
(2.495-1.55)t₂² - 3.1t₂ - 1.55 = 0
0.905t₂² - 3.1t₂ - 1.55 = 0 Quadratic equation
Solving the quadratic equation we have:
(a) t₂ = 3.87 s : time at which Kathy overtakes Stan
(b) Distance in which Kathy catches Stan
we replace t₂ = 3.87 s in equation 2
d₂ = 2.495*( 3.87)²
d₂ = 37.36 m
(c) Speeds of both cars at the instant Kathy overtakes Stan
We apply the Formula (1)
vf₁= v₀₁+a₁t₁ t₁ =( t₂+1 ) s=( 3.87 + 1 ) s = 4.87 s
vf₁= 0+3.1* 4.87
vf₁ = 15.097 m/s : Stan's final speed
vf₂ = v₀₂+a₂ t₂
vf₂ =0+4.99* 3.87
vf₂ = 19.31m/s : Kathy's final speed
Answer:
ac = 204 [m/s²]
Explanation:
To solve this problem we must use the following equation that relates the tangential velocity to the radius of rotation.
ac = v²/r
where:
v = tangential velocity = 15 [m/s]
r = radius = 1.1 [m]
Now replacing we have:
ac = (15)²/1.1
ac = 204 [m/s²]
Answer:
Explanation:
Area of crossection, A = 7.80 cm²
Initial magnetic field, B = 0.5 T
Final magnetic field, B' = 3.3 T
Time, t = 1 s
resistance of the coil, R = 1.2 ohm
The induced emf is given by
where, Ф is the rate of change of magnetic flux.
e = 7.80 x 10^-4 x (3.3 - 0.5) / 1
e = 2.184 mV
i = e/R
i = 2.184/1.2
i = 1.82 mA
Answer:
9.93 MPa
Explanation:
Given:
- mass of the man = 68.4 kg
- Deflection dx = 5.2 cm
- thickness of plank t = 2.0 cm
- width of plank w = 13.0 cm
- Length subtended L = 2.0 m
Find:
Shear Modulus of Elasticity S :
S = shear stress / shear strain
Shear stress = F / A
Shear stress = 68.4*9.81 / 0.02*0.13
Shear stress = 258078.4615 Pa
Shear strain = dx / L
Shear Strain = 0.052 / 2
Shear Strain = 0.026
Hence,
S = 258078.4615 / 0.026
S = 9.93 MPa
Answer:
i believe that it is d
Explanation:
In a super heater, the temperature of the steam rises while the pressure remains constant. This process helps to remove the last traces of moisture from the saturated steam.
In a super heater, the conclusion is that option (C) pressure remains constant and temperature rises is the correct choice. A super heater is a device used in a steam power plant to increase the temperature of the steam, above its saturation temperature. The function of the super heater is to remove the last traces of moisture (1 to 2%) from the saturated steam and to increase its temperature above the saturation temperature. The pressure, however, remains constant during this process because the super heater operates at the same pressure as the boiler.
#SPJ2
Answer:
elative magnitude of the two forces is the same and they are applied in a constant direction.
Explanation:
Newton's second law states that the sum of the forces is equal to the mass times the acceleration
∑ F = m a
in this case there are two forces on the x axis
F_applied - fr = 0
since they indicate that the velocity is constant, consequently
F_applied = fr
the relative magnitude of the two forces is the same and they are applied in a constant direction.